2015
DOI: 10.7314/apjcp.2015.16.13.5385
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcomes of Gastric Cancer at a University Teaching Hospital in Nepal

Abstract: Background: Gastric cancer is the most common gastrointestinal cancer and a leading cause of cancer mortality in Nepal. Survival of gastric cancer patients depends on the stage at which diagnosis is made. The aim of this study was to analyze the presentation and outcomes of gastric cancer patients treated at a tertiary care hospital in Nepal. Materials and Methods: A retrospective analysis of 140 consecutive histologically proven gastric adenocarcinoma cases managed at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
3
3
0
Order By: Relevance
“…After analyzing the histological subtypes of the gastric cancer specimens, gastric adenocarcinoma was found in 90.0% cases whereas, non-Hodgkin lymphomas was seen in 10.0% cases. Similar to our study, Kassim et al 11 and Shah et al 12 reported majority of the gastric cancers with adenocarcinoma type comprising of 75.3% and 92.4% of total cases.…”
Section: Discussionsupporting
confidence: 92%
“…After analyzing the histological subtypes of the gastric cancer specimens, gastric adenocarcinoma was found in 90.0% cases whereas, non-Hodgkin lymphomas was seen in 10.0% cases. Similar to our study, Kassim et al 11 and Shah et al 12 reported majority of the gastric cancers with adenocarcinoma type comprising of 75.3% and 92.4% of total cases.…”
Section: Discussionsupporting
confidence: 92%
“…11 In a study done in Nepal more than half of the patients (55.7%) were in age group of 50-70 years with the mean age of 59.6 years and male to female ratio of 2:1. 12 Similar finding was observed in other study which showed 80.5% patients of more than 45 years and male to female ratio was 1.97:1. 13 Our study also showed similar results with 72.5 % patients more than 50 patients and male to female ratio of 1.7:1.…”
Section: Discussionsupporting
confidence: 88%
“…In India there is considerable variation among registries in this cancer (Nandakumar et al, 2005;Moore et al, 2010). Gastric cancer in Nepal is usually diagnosed at an advanced stage and has a poor prognosis, so that early detection is the key to improve the survival (Sah et al, 2015). The relatively low incidence of gastric cancer in Nepal can be attributed to low gastric mucosal atrophy, but mountainous subjects have highrisk gastric mucosal status, which could be considered a high-risk population in Nepal (Miftahussurur et al, 2015).…”
Section: Discussionmentioning
confidence: 99%